Highly Reversible Li–Se Batteries with Ultra-Lightweight N,S-Codoped Graphene Blocking Layer - Gu, Xingxing; Xin, Lingbao; Li, Yang; Dong, Fan; Fu, Min; Hou, Yanglong (Nano-Micro Letters, 2018)
The desire for practical utilization of rechargeable lithium batteries with high energy density has motivated attempts to develop new electrode materials and battery systems. Here, without additional binders we present a simple vacuum filtration method to synthesize nitrogen and sulfur codoped graphene (N,S-G) blocking layer, which is ultra-lightweight, conductive, and free standing. When the N,S-G membrane was inserted between the catholyte and separator, the lithium–selenium (Li–Se) batteries exhibited a high reversible discharge capacity of 330.7 mAh g−1 at 1 C (1 C = 675 mA g−1) after 500 cycles and high rate performance (over 310 mAh g−1 at 4 C) even at an active material loading as high as 5 mg cm−2. This excellent performance can be ascribed to homogenous dispersion of the liquid active material in the electrode, good Li+-ion conductivity, fast electronic transport in the conductive graphene framework, and strong chemical confinement of polyselenides by nitrogen and sulfur atoms. More importantly, it is a promising strategy for enhancing the energy density of Li–Se batteries by using the catholyte with a lightweight heteroatom doping carbon matrix. Highlights: 1 A free-standing, ultra-lightweight, N,S-codoped graphene membrane is assembled by a simple vacuum filtration method. 2 The N,S-codoped graphene membrane is first used as the blocking layer for a polyselenide catholyte. 3 The Li–Se batteries based on the as-prepared graphene membrane exhibites excellent cycling performance and rate capability at high selenium loading (5 mg cm−2).